AB0748 Carbimazole induced ANCA associated renal vasculitis. (23rd January 2014) - Singh, D.; Jayashekara, A.; Kaplan, F.
Abstract : Background: We present a case of renal antineutrophil cytoplasmic antibody (ANCA)-associated-vasculitis (AAV) precipitated following introduction of carbimazole while treating hyperthyroidism. Methods: A 22 yr old female was newly diagnosed with thyrotoxicosis with raised free thyroxine (16.8 pmol/L) and suppressed thyroid-stimulating-hormone (<0.03mIU/L). She was started on anti-thyroid drug Carbimazole 20 mg. A fortnight later she presented with systemic symptoms of nausea, vomiting, fever with rigors and weight-loss associated with self-limiting maculo-papular skin-rash. Her renal-functions were deranged with a creatinine of 704umol/land urea 20mmol/l, which worsened over the next 48 hours. Her ultrasound of renal-tract demonstrated bilateral oedematous kidneys. She needed high-dependency-unit support for renal replacement therapy using haemodialysis following a seizure. She was cytoplasmic-ANCA positive with raised proteinase-3 (titers 28AU/ml). Her myeloperoxidase titres were <7 (AU/ml) She was negative for anti-thyroid-stimulating-hormone-receptor antibodies, anti-thyroid-peroxidase antibody, anti-glomerular-basement-membrane antibody and for anti-nuclear-antibodies with normal serum-complement levels. Results: Thionamides drugs are proposed to provoke AAV; therefore it was thought that perhaps this could be carbimazole-induced renal AAV; hencecarbimazole was withdrawn. Subsequently the renal biopsy(see Image 1 silver stain with glomerulus showing fibrinoid necrosis surrounded by cellular crescent) revealed concentric necrotizing-glomerulonephritis consistent with c-ANCA positive-vasculitis. She was further treated with high dose prednisolone and cyclophosphamide following which her renal function improved. She was weaned off haemodialysis and her thyroid function tests also normalized without any further anti-thyroid therapy. Although exact mechanism is not known it is well known that the altered immune environment associated with autoimmune thyroid disease is not sufficient to develop ANCA but treatment with thionamides (which accumulate in neutrophils) is important in promoting ANCA development. There is only limited literature available describing carbimazole-induced-ANCA-positive renal vasculitis; and as in other case reports, renal function improved after carbimazole discontinuation and provision of immunosuppressive therapy. Conclusions: Our case report re-iterates that physicians should maintain a high index for suspicion of AAV as a potentially life-threatening adverse effect in patients receiving carbimazole who develop systemic disease consistent with vasculitis. Disclosure of Interest: None Declared